2013
DOI: 10.1159/000354249
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparison of Medical Costs Shared by Payers and Patients: A Study of Postmenopausal Women with Early-Stage Breast Cancer Based on Assumption Case Scenarios and Reimbursement Fees

Abstract: Background: The objectives of this study were to estimate and cross-nationally compare the medical costs shared by payers and patients and the distributions of medical costs by cost category. Material and Methods: We estimated the medical costs covered from definitive diagnosis to completion of treatments of early-stage breast cancer and follow-up, assuming almost identical medical care provided in Japan, the UK, and Germany. The analysis was performed from the payer's perspective. Medical costs were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
1
0
3
Order By: Relevance
“…En coherencia con lo encontrado en la literatura 2,11,12 los dos determinantes principales del coste total del cáncer de mama son el tratamiento inicial de los estadíos I a III y el coste del estadío IV. Entre todos generan la mayor parte del coste del tratamiento del CM.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En coherencia con lo encontrado en la literatura 2,11,12 los dos determinantes principales del coste total del cáncer de mama son el tratamiento inicial de los estadíos I a III y el coste del estadío IV. Entre todos generan la mayor parte del coste del tratamiento del CM.…”
Section: Discussionunclassified
“…La carga económica de la asistencia sanitaria del cáncer de mama (CM) es importante para el sistema sanitario tanto por su alta incidencia, ya que es el tumor maligno más frecuente y la primera causa de muerte por cáncer en la población femenina, como por el coste de sus tratamientos [1][2][3] . La introducción de nuevas terapias tiene que basarse en la medición de su eficiencia y para ello es indispensable disponer del conocimiento detallado del consumo de recursos asociado 4 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…According to the defined inclusion and exclusion criteria, 244 articles were excluded after reviewing the title and abstract and Seven articles were costing studies evaluating BC costs in the German context. Out of the seven, five studies (40,(43)(44)(45)(46) used case scenarios based on German S3 BC treatment guidelines and other sources from the literature, and costs were calculated mainly using predefined national tariffs such as the DRG (diagnosis-related groups) for inpatient care, the EBM (German Uniform Evaluation Standard) for outpatient care and the Rote Liste for drug prices (40,(43)(44)(45)(46). These studies reported a BC cost per patient; however, the estimates cannot be linked to the disease stages.…”
Section: Systematic Reviewmentioning
confidence: 99%